Factors Associated with Pulmonary Tuberculosis Patients Who Received Anti-TB Treatment - Zubaidah, Tien; Setyaningrum, Ratna; Ratodi, Muhamad; Munir, Misbakhul (International Conference on Sustainable Health Promotion, 2018)
Pulmonary tuberculosis is a chronic infectious disease that was firmly related to the environment and human behavior. To overcome pulmonary tuberculosis, various factors associated with TB who received anti-TB treatment became significant. Therefore, we extended the Riskesdas data analysis To determine the various factors related to Pulmonary TB patients received anti-TB treatment. Subject treated with anti-TB treatment became the dependent variable, while the independent variables consisted of subjects characteristics (age, gender, and education level), socio-economic status and residential classification. Logistic regression was used to identify factors associated with the use of anti-tuberculosis. The result showed that male subjects with age of 35 until 44 years, low education, consider poor in economic and inhabited in an urban area more common in subjects with anti-TB treatment. Thus, characteristics of subjects (age, gender, and education level), socio-economic status and residential classification are the factors of subjects treated with anti-tuberculosis in Indonesia.